2019
DOI: 10.1101/754077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstruction of plant–pollinator networks from observational data

Abstract: Empirical measurements of ecological networks such as food webs and mutualistic networks are often rich in structure but also noisy and error-prone, particularly for rare species for which observations are sparse. Focusing on the case of plant-pollinator networks, we here describe a Bayesian statistical technique that allows us to make accurate estimates of network structure and ecological metrics from such noisy observational data. Our method yields not only estimates of these quantities, but also estimates o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…For instance, the map equation assumes complete data and, when networks are sparse and may contain missing links, the optimal solution is distorted (Smiljanić et al, 2020). To overcome these obstacles, further investigation should consider the use of improved flow-based community detection algorithms in development (Smiljanić et al, 2020;Young et al, 2020Young et al, , 2021.…”
Section: Appendix 3: Sampling Coverage Of Caracoles (2020)mentioning
confidence: 99%
“…For instance, the map equation assumes complete data and, when networks are sparse and may contain missing links, the optimal solution is distorted (Smiljanić et al, 2020). To overcome these obstacles, further investigation should consider the use of improved flow-based community detection algorithms in development (Smiljanić et al, 2020;Young et al, 2020Young et al, , 2021.…”
Section: Appendix 3: Sampling Coverage Of Caracoles (2020)mentioning
confidence: 99%
“…As is the case with most empirical networks, sampling of interactions in biological surveys is incomplete in our dataset. Studies show that sampling bias tends to strongly underestimate the number of interactions and overestimate the degree of specialization Young et al, 2019). To obtain a more reliable picture of pollination interactions across the AF, we applied a method of network reconstruction based on stochastic blockmodels to our metanetwork.…”
Section: Interaction Network Reconstructionmentioning
confidence: 99%
“…Network inference techniques developed in the domain of Network Science can help in the reconstruction of incomplete data (e.g. Peixoto 2018, Young et al 2019, allowing us to capture patterns at a large scale, gain further insight into ecosystem functioning, and hopefully build better conservation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies based on empirical observations of mutualism have revealed recurrent network patterns of these many-to-many interactions 12 , 13 . In a synthesis of these studies, Fernanda Valdovinos 28 , 29 highlighted five structural properties shared by mutualistic networks:…”
Section: Introductionmentioning
confidence: 99%